(untitled) (Raparin Journal of Humanities (RJH), 2025)
Language and speech, in their most basic definitions, are considered tools for communication. This communication manifests on two levels: respect and appreciation on one hand, and disrespect and humiliation on the other. Each level is used in specific contexts and situations. Respect is shaped by factors such as environment, education level, and an individual’s approach to social interactions. In contrast, disrespect encompasses swearing, cursing, and offensive language, both in speech and writing. It is influenced by various factors, including hopelessness, insult, and the insult of another’s character. Disrespect is commonly observed in daily speech, used by individuals across different social statuses for reasons such as mockery, character assassination, trivialization, and criticism. Literature and folklore—including stories, proverbs, music, riddles, and epigrams—are rich with expressions of disrespect. This phenomenon does not emerge out of nowhere but is rather a response to certain behaviors, events, and circumstances. People resort to disrespect to challenge or diminish others’ claims. Notably, disrespect is frequently observed in folklore and riddles due to their nature and characteristics. This research aims to examine the presence of disrespect in language, particularly in riddles, as riddles often stem from unmet hopes and desires, leading to expressions of disdain.